Creative Variations in Altaf Fatima’s Novels - Saleem, Irum; Kokab, Farzana; Parveen, Azra (sourcecoder, 2022)
Due to the diversity of her work, Altaf Fatima holds a significant position in Urdu literature. Her work represents the voice of her era and the true center of Urdu literature. Through her novels, she has displayed her uniqueness on a thematic and stylistic level. Altaf Fatima’s initial novels are romantic, while the last novels have a tendency towards reality.